Phosphorus alloy frame composite material, preparation method thereof, pole piece and battery
By preparing phosphorus alloy frame composite materials, combined with the unique structure of tin-based alloy frame, graphene oxide and phosphorus, the problem that phosphorus conductivity, cycling performance and rate performance in the battery cannot be met at the same time, and a significant improvement in battery performance has been achieved .
Patent Information
- Application Number
- CN202510018668.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-02-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the prior art, the conductivity, cycling performance and rate performance of phosphorus in the negative electrode material cannot be met at the same time, resulting in insufficient performance in battery applications.
By preparing a phosphorus alloy frame composite material, including a tin-based alloy frame, graphene oxide and phosphorus, graphene oxide is interspersed in the tin-based alloy frame, and phosphorus is distributed on the surface of the tin-based alloy frame, and the folds of graphene oxide are added. The surface of graphene oxide. The composite material further optimizes its structure and performance through heat treatment and cooling processes.
The phosphorus alloy frame composite material exhibits excellent conductivity, cycling performance and rate performance in the battery, significantly improving the overall performance of the battery.
Smart Images

Figure CN119481017A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a phosphorus alloy frame composite material and a preparation method thereof, a pole piece and a battery. Background Art
[0002] Lithium-ion batteries currently dominate the power supply of portable electronic devices and have been integrated into (plug-in hybrid) electric vehicles to reduce energy dependence on fossil fuels. The limited energy density of current carbon-based materials is no longer sufficient to meet the market demand for the next generation of lithium-ion batteries with high energy and high power density requirements. Phosphorus is considered to be one of the most promising alternative materials for the next generation, with red phosphorus having a theoretical capacity of up to 2596 mAh / g, which is 7 times that of graphite. However, phosphorus has been hindered in practical applications due to its poor electrical conductivity (10-12 S / m) and huge volume expansion changes (over 300%).
[0003] Chinese patent CN 113675409 A introduces a phosphorus-metal organic framework composite material and its preparation method. First, red phosphorus is placed under an inert gas for mechanical grinding, and a nickel metal organic framework is prepared simultaneously. After the two are evenly mixed, a hydrothermal method is used in combination with a drying step to obtain a phosphorus-metal organic framework composite material. Although the composite material obtained by this method can alleviate the conductivity and rate performance of phosphorus to a certain extent, the improvement of the cycle performance by this method is still limited, resulting in a capacity retention rate of only 70% after 50 cycles, that is, the patent cannot simultaneously meet certain conductivity, cycle performance and rate performance. Summary of the invention
[0004] In order to overcome the defect that the conductivity, cycle performance and rate performance cannot be simultaneously satisfied when phosphorus is used as negative electrode materials in the prior art, the present invention provides a phosphorus alloy frame composite material and a preparation method thereof, a pole piece and a battery. The phosphorus alloy frame composite material has excellent conductivity, and when used in a battery, has excellent cycle performance and rate performance.
[0005] The present invention solves the above technical problems through the following technical solutions.
[0006] The present invention provides a phosphorus alloy frame composite material, which comprises a tin-based alloy frame, graphene oxide and phosphorus, wherein the graphene oxide is interspersed in the tin-based alloy frame, and the phosphorus is distributed on at least one of the surface of the tin-based alloy frame, in the wrinkles of the graphene oxide and on the surface of the graphene oxide;
[0007] The tin-based alloy framework comprises tin nanoparticles and transition metal nanoparticles, and the tin nanoparticles and the transition metal nanoparticles are connected by using cyano groups as bridges.
[0008] In the present invention, preferably, the phosphorus is distributed on the surface of the tin-based alloy frame, in the wrinkles of the graphene oxide, and on the surface of the graphene oxide.
[0009] In the present invention, preferably, the D50 particle size of the phosphorus alloy frame composite material is 385-450nm.
[0010] In the present invention, preferably, the transition metal of the transition metal nanoparticles is selected from one or more of Ni, Fe, Co and Cu.
[0011] In the present invention, preferably, the phosphorus content in the phosphorus alloy frame composite material is 35%-38%, for example, 35.1%, 36.3%, 36.8%, 36.9%, 37.1%, 37.2% or 37.5%, where the percentage is the mass percentage of the phosphorus alloy frame composite material.
[0012] In the present invention, preferably, the tin content in the phosphorus alloy frame composite material is 27%-29%, for example, 27.2%, 27.3%, 27.4%, 27.6%, 27.7%, 27.9% or 28.1%, where the percentage is the mass percentage of the phosphorus alloy frame composite material.
[0013] In the present invention, preferably, in the phosphorus alloy framework composite material, the transition metal content of the transition metal nanoparticles is 15%-17%, for example, 15.9%, 16.0%, 16.1%, 16.2%, 16.3%, 16.5% or 16.8%, where the percentage is the mass percentage of the phosphorus alloy framework composite material.
[0014] In certain specific embodiments of the present invention, the phosphorus of the phosphorus alloy framework composite material accounts for 35%-38% by mass of the phosphorus alloy framework composite material, the tin of the phosphorus alloy framework composite material accounts for 27%-29% by mass of the phosphorus alloy framework composite material, and the transition metal of the transition metal nanoparticles of the phosphorus alloy framework composite material accounts for 15%-17% by mass of the phosphorus alloy framework composite material.
[0015] In the present invention, preferably, the phosphorus alloy frame composite material also includes carbon, and the carbon content is 8%-10%, for example, 8.8%, 8.9%, 9.2%, 9.3%, 9.4%, 9.5% or 9.9%, where the percentage is the mass percentage of the phosphorus alloy frame composite material.
[0016] In the present invention, preferably, the phosphorus alloy frame composite material also includes nitrogen, and the nitrogen content is 0.4%-0.7%, for example, 0.43%, 0.49%, 0.52%, 0.53%, 0.54%, 0.61%, 0.65% or 0.69%, where the percentage is the mass percentage of the phosphorus alloy frame composite material.
[0017] In the present invention, the tin-based alloy framework further comprises M' nanoparticles, and the tin nanoparticles, transition metal nanoparticles and M' nanoparticles are connected by cyano groups; wherein M' is selected from one or more elements of In, Pt, Pd, Sb and Ge.
[0018] Preferably, the mass percentage of the M' nanoparticles in the phosphorus alloy frame composite material is 9%-10%, for example, 9.1%, 9.2%, 9.3%, 9.4%, 9.5% or 9.7%.
[0019] The present invention also provides a method for preparing a phosphorus alloy frame composite material, which comprises the following steps:
[0020] S1: mixing the first solution and the third solution to obtain a wet gel;
[0021] The first solution includes tin halide, and the third solution includes a cyano compound containing a transition metal; the first solution and / or the third solution includes phosphorus-containing graphene oxide; the phosphorus-containing graphene oxide is obtained by mechanical grinding of graphene oxide and phosphorus;
[0022] S2: the wet gel and the sodium borohydride solution undergo a reduction reaction and then dry to obtain a phosphorene cyanide xerogel;
[0023] S3: heat-treating and cooling the phosphorene cyanide xerogel in sequence to obtain the phosphorus alloy frame composite material; the temperature of the heat treatment insulation stage is 400-550°C, and the temperature of the cooling insulation stage is 240-280°C.
[0024] In the present invention, the tin halide means a compound containing halogen and tin element.
[0025] In the present invention, preferably, the tin halide is SnCl4.
[0026] In the present invention, the transition metal-containing cyano compound means a compound containing both a transition metal and a cyano group.
[0027] In the present invention, preferably, the transition metal of the transition metal-containing cyano compound is selected from one or more of Ni, Fe, Co and Cu.
[0028] Preferably, the chemical formula of the transition metal-containing cyano compound is K y M(CN) z , wherein M is selected from one or more of Ni, Fe, Co and Cu.
[0029] Preferably, y satisfies: 0<y<6.
[0030] Preferably, z satisfies: 3<z<8.
[0031] In the present invention, in the wet gel, the molar ratio of tin element to transition metal is preferably (1.5-2.5):(1-1.5), for example, 2:1.3 or 2:1.
[0032] In the present invention, preferably, the concentration of the phosphorus-containing graphene oxide in the wet gel is 20-90 mg / mL, more preferably 20-30 mg / mL, for example 25 mg / mL, 27.4 mg / mL, 29.5 mg / mL or 30.5 mg / mL.
[0033] In the present invention, preferably, in the wet gel, the molar ratio of tin element to cyano group is (1.5-2.5):(3-12), for example, 2:7.8 or 1:3.
[0034] In the present invention, preferably, the first solution includes phosphorus-containing graphene oxide.
[0035] Preferably, the concentration of the phosphorus-containing graphene oxide in the first solution is 20-30 mg / mL, for example, 25 mg / mL.
[0036] In the present invention, preferably, the concentration of the tin halide in the first solution is 0.4-1 mol / L, preferably 0.8 mol / L.
[0037] In some specific embodiments of the present invention, the solvent of the first solution is dimethylamide solution.
[0038] In the present invention, preferably, the third solution includes phosphorus-containing graphene oxide.
[0039] Preferably, the concentration of the phosphorus-containing graphene oxide in the third solution is 30-60 mg / mL, more preferably 30-50 mg / mL.
[0040] In the present invention, preferably, the concentration of the cyano compound containing the transition metal in the third solution is 0.4-1 mol / L, preferably 0.8 mol / L.
[0041] In certain specific embodiments of the present invention, the third solution is prepared by dispersing the phosphorus-containing graphene oxide in the solution of the transition metal-containing cyano compound by ultrasonication.
[0042] In the present invention, preferably, step S1 comprises: mixing the first solution, the second solution and the third solution to obtain a wet gel; the second solution comprises a compound containing an M' element; wherein M' is selected from one or more elements of In, Pt, Pd, Sb and Ge.
[0043] Preferably, the compound containing the M' element is a chloride containing the M' element, and the chemical formula of the chloride containing the M' element is M'Cl x .
[0044] Preferably, x satisfies: 2≤x<6.
[0045] Preferably, the concentration of the compound containing the M' element in the second solution is 0.4-1 mol / L, preferably 0.8 mol / L.
[0046] In some specific embodiments of the present invention, the solvent of the second solution is dimethylamide solution.
[0047] Preferably, in the wet gel, the molar ratio of the tin element to the M' element is (1.5-2.5):(0.5-1), for example, 2:0.9.
[0048] In the present invention, the method for preparing graphene oxide preferably adopts the Hummer method, and its specific steps include, for example:
[0049] Graphene oxide is obtained by mixing graphene and an oxidant to undergo an oxidation reaction; the oxidant includes potassium permanganate and sodium nitrate.
[0050] The mass ratio of the graphene to the potassium permanganate is preferably (2-4):(3-7), for example, 2.5:4.5 or 3.5:4.5.
[0051] The mass ratio of the graphene to the sodium nitrate is preferably (2-4):(0.5-1.5), for example, 2.5:1 or 3.5:1.
[0052] Preferably, the graphene and the oxidant are mixed under the condition of sulfuric acid as a solvent.
[0053] The concentration of the sulfuric acid is preferably 85%-98%, for example 98%.
[0054] Preferably, the oxidation reaction includes a first reaction stage, a second reaction stage and a third reaction stage in sequence; wherein the temperature of the first reaction stage is 2-5°C, for example, 3°C, the temperature of the second reaction stage is 30-40°C, for example, 35°C, and the temperature of the third reaction stage is 90-100°C, for example, 95°C.
[0055] The time of the first reaction stage is preferably 2-4 hours, for example 3.5 hours.
[0056] The second reaction stage preferably lasts for 5-6 hours, for example, 5.5 hours.
[0057] There is no particular limitation on the time of the third reaction stage, as long as the reaction liquid turns into golden yellow.
[0058] In certain specific embodiments of the present invention, the oxidation reaction further includes washing and drying in sequence to obtain graphene oxide.
[0059] The washing may be conventional in the art, for example, comprising the following steps: the reaction solution obtained after the oxidation reaction is centrifuged and washed multiple times in a centrifuge.
[0060] The number of washings is not particularly limited, so that there is no SO4 in the reaction solution. 2- SO4 in the reaction solution 2- The detection can be carried out in the following way: Mix the reaction solution with BaCl2. If no white precipitate is generated, it indicates that there is no SO4 in the reaction solution. 2- .
[0061] The drying temperature is preferably 40-85°C, more preferably 40-50°C.
[0062] The drying time is preferably 1-12 hours, more preferably 1-2 hours.
[0063] In the present invention, after mechanical grinding, part of the phosphorus element can enter the wrinkles of graphene oxide to form phosphorus-containing graphene oxide. The phosphorus-containing graphene oxide means graphene oxide containing phosphorus, and the phosphorus element can be distributed in the wrinkles of graphene oxide and / or on the surface of graphene oxide.
[0064] In the present invention, the graphene oxide has a wrinkled structure.
[0065] In the present invention, preferably, the phosphorus element is red phosphorus.
[0066] In the present invention, preferably, the mass ratio of the phosphorus element to the graphene oxide is (8-10):(1-3), for example, 10:1.5 or 8.5:1.5.
[0067] In the present invention, preferably, the mechanical mill is a ball mill.
[0068] Preferably, the rotation speed of the ball mill is 450-650 r / min, for example, 500 r / min or 550 r / min.
[0069] Preferably, the ball milling time is 9-15 hours, for example, 12 hours.
[0070] In certain specific embodiments of the present invention, the ball milling is performed under an inert gas environment.
[0071] The inert gas is, for example, one or more of argon, helium, neon and nitrogen.
[0072] The purity of the nitrogen is preferably above 99.99%.
[0073] In certain specific embodiments of the present invention, the ball milling is performed in a ball milling jar.
[0074] In the present invention, the concentration of the sodium borohydride solution is preferably 1-3 mol / L, for example 2 mol / L.
[0075] In the present invention, the reduction reaction time is preferably 2-3 hours, for example 2.5 hours.
[0076] In the present invention, the drying method is preferably freeze drying, CO2 supercritical drying or vacuum drying.
[0077] Wherein, when freeze-drying is used: the drying temperature is preferably -30~-80°C; the drying time is preferably 3-7h.
[0078] Wherein, when CO2 supercritical drying is used: the drying temperature is preferably 10-40°C; the drying time is preferably 1-3h; and the drying pressure is 10-15kPa.
[0079] Wherein, when vacuum drying is used: the drying temperature is preferably 80-100° C.; the drying time is preferably 12-32 hours.
[0080] In step S3 of the present invention, after the phosphorene cyanide xerogel is heat-treated and cooled in sequence, the phosphorus element therein first volatilizes into the environment and is uniformly deposited in the phosphorus alloy framework composite material during cooling.
[0081] In the present invention, the temperature of the heat treatment in the insulation stage is preferably 450-520°C, for example 460°C or 500°C.
[0082] In the present invention, preferably, the heat preservation stage of the heat treatment lasts for 6-10 hours, for example, 9 hours.
[0083] In the present invention, preferably, the rate of the heating stage of the heat treatment is 1-3°C / min, for example, 2°C / min.
[0084] In the present invention, preferably, the heat treatment pressure is 1-10Mpa.
[0085] In the present invention, the cooling includes a constant temperature stage and a temperature reduction stage in sequence.
[0086] In the present invention, preferably, the cooling and heat preservation stage lasts for 18-28 hours, such as 24 hours or 26 hours.
[0087] In the present invention, preferably, the temperature of the cooling and heat preservation stage is 260°C.
[0088] In the present invention, preferably, the cooling rate in the temperature reduction stage is preferably 5-10°C / min, for example 8°C / min.
[0089] In certain specific embodiments of the present invention, the cooling is performed under an inert gas environment.
[0090] The inert gas is, for example, one or more of argon, helium, neon and nitrogen.
[0091] The purity of the nitrogen is preferably above 99.99%.
[0092] In certain specific embodiments of the present invention, the heat treatment is performed in an inert gas environment.
[0093] The inert gas is, for example, one or more of argon, helium, neon and nitrogen.
[0094] The purity of the nitrogen is preferably above 99.99%.
[0095] In the present invention, preferably, after the cooling, the steps of first washing, first drying, second washing and second drying are sequentially included to obtain the phosphorus alloy frame composite material.
[0096] The detergent used in the first washing is, for example, distilled water and ethanol, wherein the distilled water and ethanol are used in excess to remove residual KCl crystals.
[0097] The first drying temperature is preferably 80-100°C, for example 85°C.
[0098] The first drying time is preferably 10-20 hours, for example 16 hours.
[0099] The detergent for the second washing is, for example, carbon disulfide.
[0100] The second drying temperature is preferably 80-100°C, for example 85°C.
[0101] The second drying time is preferably 20-32 hours, for example 24 hours.
[0102] The drying method is preferably freeze drying, CO2 supercritical drying or vacuum drying.
[0103] Wherein, when freeze-drying is used: the drying temperature is preferably -30~-80°C; the drying time is preferably 3-7h.
[0104] Wherein, when CO2 supercritical drying is used: the drying temperature is preferably 10-40°C; the drying time is preferably 1-3h; and the drying pressure is 10-15kPa.
[0105] Wherein, when vacuum drying is used: the drying temperature is preferably 80-100° C.; the drying time is preferably 12-32 hours.
[0106] The present invention also provides a phosphorus alloy frame composite material prepared by the preparation method of the phosphorus alloy frame composite material.
[0107] In the present invention, the D50 particle size of the phosphorus alloy framework composite material may be 385-450 nm.
[0108] The present invention also provides a pole piece, which comprises the above-mentioned phosphorus alloy frame composite material.
[0109] The present invention also provides a battery, which comprises the above-mentioned pole piece.
[0110] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0111] The reagents and raw materials used in the present invention are commercially available.
[0112] The positive and progressive effects of the present invention are:
[0113] The phosphorus alloy framework composite material provided by the present invention combines graphene oxide and phosphorus with a metal network framework. The wrinkled structure of graphene oxide can improve the problem of high volume expansion of phosphorus. The unique structure of the metal network framework allows graphene oxide and phosphorus to exist in its network structure, which can improve the problems of low conductivity and high volume expansion of phosphorus. Graphene oxide and the metal network framework not only improve the problems of low conductivity and high volume expansion of phosphorus, but also further improve the cycle performance and rate performance.
[0114] The phosphorus alloy framework composite material of the invention has excellent electrical conductivity and has excellent cycle performance and rate performance when used in a battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0115] Figure 1 This is a flow chart for preparing the phosphorus alloy frame composite material of Example 1. DETAILED DESCRIPTION
[0116] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0117] Graphene was purchased from Suzhou Qingtan Nanomaterials Co., Ltd., model number 1034343-98-0;
[0118] Red phosphorus was purchased from Wuhan Kanosi Technology Co., Ltd., model number 7723-14.
[0119] Example 1
[0120] Preparation of phosphorus-containing graphene oxide:
[0121] Preparation of graphene oxide: Graphene, potassium permanganate and sodium nitrate are added to concentrated sulfuric acid in a mass ratio of 2.5:4.5:1, and the concentration of concentrated sulfuric acid is 98%; after oxidation at 3°C for 3.5 hours, the temperature is raised to 35°C and oxidation is continued for 5.5 hours, and further oxidation is performed at 95°C until the reaction solution turns golden yellow; the solution after the reaction is centrifuged and washed several times in a centrifuge until no white precipitate is generated when the reaction solution and BaCl2 are mixed, and dried at 85°C for 12 hours to obtain graphene oxide.
[0122] Red phosphorus and the above-mentioned graphene oxide are placed in a ball mill according to a mass ratio of 8.5:1.5. The ball mill environment is filled with inert gas argon. The ball mill speed is 500r / min and the ball mill time is 12h to obtain phosphorus-containing graphene oxide.
[0123] Preparation of phosphorus alloy frame composite materials:
[0124] S1: Preparation of wet gel:
[0125] The first solution, the second solution and the third solution are mixed to obtain a wet gel; the molar ratio of the tin element, the Ge element and the Fe element in the wet gel is 2:0.9:1.3; the concentration of the phosphorus-containing graphene oxide in the wet gel is 27.4 mg / mL;
[0126] The first solution includes SnCl4 with a concentration of 0.8 mol / L and the above-mentioned phosphorus-containing graphene oxide with a concentration of 25 mg / mL; the solvent is a dimethylamide solution; the second solution includes GeCl4 with a concentration of 0.8 mol / L; the solvent is a dimethylamide solution; the third solution includes K3Fe(CN)6 with a concentration of 0.8 mol / L and the above-mentioned phosphorus-containing graphene oxide with a concentration of 50 mg / mL; the solvent is a dimethylamide solution; the preparation method of the third solution is: dispersing the above-mentioned phosphorus-containing graphene oxide in a solution of a cyano-containing compound and dimethylamide by ultrasonication;
[0127] S2: The wet gel and 2 mol / L sodium borohydride solution were mixed to undergo a reduction reaction for 2.5 hours, and then freeze-dried at -50°C for 5 hours to obtain phosphorene cyanide xerogel;
[0128] S3: heat treating the phosphorene cyanide xerogel; the heat treatment includes a heating stage and a heat preservation stage, the heating rate is 2°C / min, the temperature of the heat preservation stage is 460°C, and the time is 9h; the heat treatment is carried out in an argon environment, and the heat treatment pressure is 1Mpa;
[0129] After the heat treatment, the mixture was cooled to 260°C at a cooling rate of 8°C / min and maintained for 24 hours. The cooling was carried out in an argon environment with a pressure of 1 MPa.
[0130] After cooling, it was repeatedly washed with distilled water and ethanol, dried at 85°C for 16 hours, and then repeatedly washed with carbon disulfide to remove white phosphorus overflowed during the heat treatment. After vacuum drying at 85°C for 24 hours, a phosphorus alloy frame composite material was obtained.
[0131] The preparation flow chart of the phosphorus alloy frame composite material of Example 1 is as follows: Figure 1 shown.
[0132] Preparation of pole piece:
[0133] The phosphorus alloy frame composite material, conductive agent (KS-6), CMC, and SBR were mixed evenly according to 95.5:1.5:1.5:1.5 and applied on the copper foil. The compaction density was 1.60 g / cm 3 , and the negative electrode sheet was obtained after vacuum drying.
[0134] Example 2
[0135] Preparation of graphene oxide:
[0136] Graphene, potassium permanganate, sodium nitrate and concentrated sulfuric acid were added into concentrated sulfuric acid in a mass ratio of 3.5:4.5:1, and the other conditions were the same as those in Example 1.
[0137] The preparation conditions of the phosphorus alloy frame composite material are the same as those in Example 1.
[0138] The preparation conditions of the electrode are the same as those in Example 1.
[0139] Example 3
[0140] Preparation of phosphorus-containing graphene oxide:
[0141] Red phosphorus and graphene oxide were placed in a ball mill at a mass ratio of 10:1.5, and the other conditions were the same as in Example 1.
[0142] The preparation conditions of the phosphorus alloy frame composite material are the same as those in Example 1.
[0143] The preparation conditions of the electrode are the same as those in Example 1.
[0144] Example 4
[0145] Preparation of phosphorus-containing graphene oxide:
[0146] The ball milling speed was 550 r / min, and the other conditions were the same as in Example 1.
[0147] The preparation conditions of the phosphorus alloy frame composite material are the same as those in Example 1.
[0148] The preparation conditions of the electrode are the same as those in Example 1.
[0149] Example 5
[0150] The preparation conditions of phosphorus-containing graphene oxide are the same as those in Example 1.
[0151] Preparation of phosphorus alloy frame composite materials:
[0152] In S1, the third solution includes 0.8 mol / L K3Fe(CN)6 and 60 mg / mL phosphorus-containing graphene oxide; the concentration of phosphorus-containing graphene oxide in the mixed solution is 30.5 mg / mL; and the other conditions are the same as in Example 1.
[0153] The preparation conditions of the electrode are the same as those in Example 1.
[0154] Example 6
[0155] The preparation conditions of phosphorus-containing graphene oxide are the same as those in Example 1.
[0156] Preparation of phosphorus alloy frame composite materials:
[0157] In S1, the first solution includes SnCl4 with a concentration of 0.8 mol / L and phosphorus-containing graphene oxide with a concentration of 20 mg / mL; the concentration of phosphorus-containing graphene oxide in the mixed solution is 25 mg / mL; and the other conditions are the same as in Example 1.
[0158] The preparation conditions of the electrode are the same as those in Example 1.
[0159] Example 7
[0160] The preparation conditions of phosphorus-containing graphene oxide are the same as those in Example 1.
[0161] Preparation of phosphorus alloy frame composite materials:
[0162] In S1, the molar ratio of the tin element, the Ge element, and the Fe element in the phosphorene cyanide gel is 2:0.9:1; the concentration of the phosphorus-containing graphene oxide in the mixed solution is 29.5 mg / mL; and the other conditions are the same as in Example 1.
[0163] The preparation conditions of the electrode are the same as those in Example 1.
[0164] Example 8
[0165] The preparation conditions of phosphorus-containing graphene oxide are the same as those in Example 1.
[0166] Preparation of phosphorus alloy frame composite materials:
[0167] In S3, the temperature of the heat-insulating stage of the heat treatment is 500°C, and the other conditions are the same as those in Example 1.
[0168] The preparation conditions of the electrode are the same as those in Example 1.
[0169] Example 9
[0170] The preparation conditions of phosphorus-containing graphene oxide are the same as those in Example 1.
[0171] Preparation of phosphorus alloy frame composite materials:
[0172] In S3, the cooling and heat preservation stage lasts for 26 hours, and the other conditions are the same as those in Example 1.
[0173] The preparation conditions of the electrode are the same as those in Example 1.
[0174] Example 10
[0175] The conditions for phosphorus-containing graphene oxide are the same as those in Example 1.
[0176] Preparation of phosphorus alloy frame composite materials:
[0177] In S3, the heat treatment pressure is 15 MPa, and the other conditions are the same as in Example 1.
[0178] The preparation conditions of the electrode are the same as those in Example 1.
[0179] The phosphorus alloy frame composite material prepared in the above embodiments 1-10 includes a tin-based alloy frame, graphene oxide and phosphorus, the graphene oxide is interspersed in the tin-based alloy frame, and the phosphorus is distributed on the surface of the tin-based alloy frame, in the folds of the graphene oxide and on the surface of the graphene oxide; the tin-based alloy frame includes tin nanoparticles and transition metal nanoparticles, and the tin nanoparticles and the transition metal nanoparticles are connected with cyanide as a bridge.
[0180] Comparative Example 1
[0181] Comparative Example 1 uses pure red phosphorus to replace the phosphorus alloy frame composite material of Example 1.
[0182] The preparation conditions of the electrode are the same as those in Example 1.
[0183] Comparative Example 2
[0184] In comparative example 2, graphene is used to replace the phosphorus alloy frame composite material of example 1.
[0185] The preparation conditions of the electrode are the same as those in Example 1.
[0186] Comparative Example 3
[0187] The preparation conditions of phosphorus-containing graphene oxide are the same as those in Example 1, and phosphorus-containing graphene oxide is used to replace the phosphorus alloy frame composite material in Example 1.
[0188] The preparation conditions of the electrode are the same as those in Example 1.
[0189] Comparative Example 4
[0190] The preparation conditions of phosphorus-containing graphene oxide are the same as those in Example 1.
[0191] Preparation of phosphorus alloy frame composite materials:
[0192] In S3, the temperature of the insulation stage is 300°C, and the other conditions are the same as in Example 1.
[0193] The preparation conditions of the electrode are the same as those in Example 1.
[0194] Effect Example 1
[0195] The phosphorus alloy frame composite materials obtained in Examples 1-10 and Comparative Examples 1-4 were subjected to the following tests:
[0196] 1. Element content test: Inductively coupled plasma (ICP) method was used for testing. The testing method was as follows: (1) Microwave digestion method was used for pretreatment. 0.5 g of the tin-carbon composite material prepared in the embodiment or comparative example was placed in a digestion tank. 3 mL of concentrated nitric acid and 9 mL of concentrated sulfuric acid were added in sequence using a liquid adder and the mixture was shaken well. The mixture was kept at 160°C for 3 min, 180°C for 3 min, 200°C for 10 min, and 220°C for 10 min in sequence. The mixture was then cooled to room temperature and filtered using quantitative filter paper. The filtrate was placed in a 50 mL volumetric flask as the test solution. (2) The test solution was tested in a PerkinElmer ICP spectrometer Avio™ 200. The test condition was an air pressure of 2.5 MPa.
[0197] 2. Conductivity test: measured at room temperature using an Orion Star™ A212 conductivity benchtop meter.
[0198] 3. Charge transfer internal resistance test: Electrochemical impedance spectroscopy (compacted density 1.65 g / cm 3 ) to obtain the charge transfer internal resistance.
[0199] 4. Particle size D50 test: The test instrument is MS3000 equipment, and the test is carried out after 1 minute of ultrasound.
[0200] The above test results are listed in Table 1:
[0201] Table 1
[0202]
[0203] Note: “ / ” in the table means that the element is not contained or the conductivity is infinitely close to 0 and can be ignored.
[0204] According to the results in Table 1, the phosphorus alloy frame composite material prepared in the embodiment of the present invention has a D50 particle size of 385-450 nm, a conductivity of more than 8.678×10^4 S / m, and a charge transfer internal resistance of less than 19.6Ω, indicating that it has excellent conductive properties.
[0205] Comparative Example 1 uses pure red phosphorus, Comparative Example 2 uses graphene, and Comparative Example 3 does not include steps S2 and S3. Replacing the phosphorus alloy frame composite material with the above materials will increase the charge transfer internal resistance.
[0206] The temperature in the insulation stage of Comparative Example 4 is too low, resulting in reduced conductivity, increased charge transfer internal resistance, and poor conductive performance.
[0207] Effect Example 2
[0208] Button battery assembly:
[0209] The pole pieces prepared in Examples 1-10 and Comparative Examples 1-4 are used as negative electrodes, lithium metal is used as the counter electrode, the electrolyte is a mixture of 1M LiPF6, ethylene carbonate (EC) and dimethyl carbonate (DMC) in a mass ratio of 1:1, and the separator is a PE / PP / PE composite film, and the button batteries can be assembled.
[0210] The button cells assembled in Examples 1-9 and Comparative Examples 1-7 were subjected to the following tests:
[0211] 1. First discharge specific capacity: Charge and discharge at a current density of 0.1mA / g-3mA / g, limit the charging voltage to 0.005-2V, and record the discharge specific capacity.
[0212] 2. First coulombic efficiency: Use constant voltage discharge mode, discharge at 0.1V / h to 0.000V, then charge at 0.1 / h to 1.5V, record the charge and discharge capacity, and obtain the first coulombic efficiency as the lithium removal capacity / lithium insertion capacity.
[0213] 3. Capacity after 300 cycles at 0.1C rate: After 300 cycles of charge and discharge at a current density of 0.1 mAh / g, the charge and discharge capacity was recorded.
[0214] 4. Expansion rate of the electrode after 300 cycles at a rate of 0.1C: The thickness of the electrode before and after 300 cycles is tested respectively. The expansion rate is calculated as: (thickness of the electrode after 300 cycles - thickness of the electrode before 300 cycles) / thickness of the electrode before 300 cycles.
[0215] 5. Capacity retention rate: The discharge capacity was tested at rates of 0.1C, 0.2C, 0.5C, 1C, 2C, 3C and 0.1C respectively, and the charging voltage was limited to 0.005-2V.
[0216] The above test results are listed in Table 2 and Table 3:
[0217] Table 2
[0218]
[0219] Table 3
[0220]
[0221] According to the results in Tables 2 and 3, when the phosphorus alloy frame composite material prepared in the embodiment of the present invention is used in a battery, its first discharge specific capacity is more than 1625 mAh / g, the first coulombic efficiency is more than 94.7%, the capacity after 300 cycles at a rate of 0.1C is more than 1341 mAh / g, the pole piece expansion rate after 300 cycles at a rate of 0.1C is less than 14.7%, and the difference in capacity retention rate of Example 1 at different rates is lower than that of the comparative example, indicating that the embodiments of the present invention have excellent cycle performance and rate performance.
[0222] Comparative Example 1 uses pure red phosphorus, Comparative Example 2 uses graphene, and Comparative Example 3 does not include steps S2 and S3. Replacing the phosphorus alloy frame composite material with the above materials will reduce the first coulomb efficiency. The first discharge specific capacity and the capacity after 300 cycles at a rate of 0.1C of Comparative Example 2 are significantly reduced. The electrode expansion rate of Comparative Examples 1 and Comparative Examples 3 after 300 cycles at a rate of 0.1C is significantly increased.
[0223] The temperature in the insulation stage of Comparative Example 4 is too low, which not only causes the conductivity to deteriorate, but also reduces the initial coulomb efficiency. After 300 cycles at a rate of 0.1C, the expansion rate of the electrode increases significantly.
Claims
1. A phosphorus alloy frame composite material, characterized in that: It includes a tin-based alloy frame, graphene oxide and phosphorus, wherein the graphene oxide is interspersed in the tin-based alloy frame, and the phosphorus is distributed on at least one of the surface of the tin-based alloy frame, the wrinkles of the graphene oxide and the surface of the graphene oxide; The tin-based alloy framework comprises tin nanoparticles and transition metal nanoparticles, and the tin nanoparticles and the transition metal nanoparticles are connected by using cyano groups as bridges.
2. The phosphorus alloy frame composite material according to claim 1, characterized in that: The phosphorus alloy frame composite material meets one or more of the following conditions: (a) The D50 particle size of the phosphorus alloy framework composite material is 385-450 nm; (b) the transition metal of the transition metal nanoparticles is selected from one or more of Ni, Fe, Co and Cu; (c) In the phosphorus alloy framework composite material, the phosphorus content is 35%-38%, the tin content is 27%-29%, and the transition metal content of the transition metal nanoparticles is 15%-17%, and the percentages are the mass percentages of the phosphorus alloy framework composite material; (d) the phosphorus alloy frame composite material further comprises carbon, the carbon content of which is 8%-10%, where the percentage is the mass percentage of the phosphorus alloy frame composite material; (e) the phosphorus alloy frame composite material further comprises nitrogen, the content of the nitrogen is 0.4%-0.7%, and the percentage is the mass percentage of the phosphorus alloy frame composite material; (f) The tin-based alloy framework further includes M' nanoparticles, and the tin nanoparticles, transition metal nanoparticles and M' nanoparticles are connected by cyano groups; wherein M' is selected from one or more elements of In, Pt, Pd, Sb and Ge.
3. A method for preparing a phosphorus alloy frame composite material, characterized in that: It includes the following steps: S1: mixing the first solution and the third solution to obtain a wet gel; The first solution includes tin halide, and the third solution includes a cyano compound containing a transition metal; the first solution and / or the third solution includes phosphorus-containing graphene oxide; the phosphorus-containing graphene oxide is obtained by mechanical grinding of graphene oxide and phosphorus; S2: the wet gel and the sodium borohydride solution undergo a reduction reaction and then dry to obtain a phosphorene cyanide xerogel; S3: heat-treating and cooling the phosphorene cyanide xerogel in sequence to obtain the phosphorus alloy frame composite material; the temperature of the heat treatment insulation stage is 400-550°C, and the temperature of the cooling insulation stage is 240-280°C.
4. The method for preparing the phosphorus alloy frame composite material according to claim 3, characterized in that: Step S1 satisfies one or more of the following conditions: (a) the tin halide is SnCl4; (b) The chemical formula of the transition metal-containing cyano compound is K y M(CN) z , wherein M is selected from one or more of Ni, Fe, Co and Cu; wherein y satisfies: 0<y<6; z satisfies: 3<z<8; (c) In the wet gel, the molar ratio of tin element to transition metal is (1.5-2.5): (1-1.5); (d) the concentration of the phosphorus-containing graphene oxide in the wet gel is 20-90 mg / mL; (e) In the wet gel, the molar ratio of tin element to cyano group is (1.5-2.5): (3-12); (f) the first solution includes phosphorus-containing graphene oxide, and the concentration of the phosphorus-containing graphene oxide in the first solution is 20-30 mg / mL; (g) the concentration of the tin halide in the first solution is 0.4-1 mol / L; (h) the third solution comprises phosphorus-containing graphene oxide, and the concentration of the phosphorus-containing graphene oxide in the third solution is 30-60 mg / mL; (i) The concentration of the transition metal-containing cyano compound in the third solution is 0.4-1 mol / L.
5. The method for preparing the phosphorus alloy frame composite material according to claim 4, characterized in that: Step S1 includes: mixing the first solution, the second solution and the third solution to obtain a wet gel; the second solution includes a chloride containing the M' element, and the chemical formula of the chloride containing the M' element is M'Cl x ; x satisfies: 2≤x<6; wherein M' is selected from one or more elements of In, Pt, Pd, Sb and Ge; Wherein, the concentration of the compound containing the M' element in the second solution is 0.4-1 mol / L; Wherein, in the wet gel, the molar ratio of the tin element to the M' element is (1.5-2.5): (0.5-1).
6. The method for preparing the phosphorus alloy frame composite material according to claim 3, characterized in that: The phosphorus-containing graphene oxide meets one or more of the following conditions: (a) The method for preparing graphene oxide comprises the following steps: mixing graphene and an oxidant to undergo an oxidation reaction to obtain graphene oxide; the oxidant comprises potassium permanganate and sodium nitrate; (b) the phosphorus element is red phosphorus; (c) the mass ratio of the phosphorus element to the graphene oxide is (8-10): (1-3); (d) The mechanical mill is a ball mill, the rotation speed of the ball mill is 450-650 r / min, and the ball milling time is 9-15 h.
7. The method for preparing the phosphorus alloy frame composite material according to claim 3, characterized in that: Step S2 and step S3 satisfy one or more of the following conditions: (a) The reduction reaction time is 2-3h; (b) the concentration of the sodium borohydride solution is 1-3 mol / L; (c) The drying method is freeze drying, CO2 supercritical drying or vacuum drying; (d) the temperature of the heat treatment holding stage is 450-520°C; (e) The heat treatment period is 6-10 hours; (f) the heating rate of the heat treatment stage is 1-3°C / min; (g) the heat treatment pressure is 1-10Mpa; (h) The cooling and heat preservation stage lasts for 18-28 hours; (i) the temperature of the cooling and holding stage is 260°C; (j) The cooling rate in the cooling stage is 5-10°C / min.
8. A phosphorus alloy frame composite material, characterized in that: The composite material is prepared by the method for preparing the phosphorus alloy frame composite material as described in any one of claims 3 to 7.
9. A pole piece, characterized in that: It comprises the phosphorus alloy frame composite material as claimed in any one of claims 1 to 2 and 8.
10. A battery, characterized in that: It comprises the pole piece as claimed in claim 9.
Citation Information
Patent Citations
Phosphorus-metal organic framework composite material and preparation method and application thereof
CN113675409A
Battery negative material as well as preparation and application thereof
CN108232132A
Red phosphorus / nitrogen-doped graphene composite negative electrode material, method for preparing same and application of red phosphorus / nitrogen-doped graphene composite negative electrode material
CN108376767A
Phosphorus-based negative electrode material and preparation method thereof, negative electrode and lithium ion battery
CN109216682A
Phosphorus-carbon composite material as well as preparation method and application thereof
CN116768195A